A broadband inverted umbrella shaped cylindrical dielectric resonator antenna for "WLAN" and "C" band applications. Issue 6 (11th February 2017) - Vinodha, E.; Raghavan, S.
Abstract: The main objective of the present article is to improve the bandwidth of a low profile Cylindrical Dielectric Resonator Antenna (CDRA) and operate it for WLAN and "C" band applications. An inverted umbrella shaped CDRA excited by a microstrip feedline with single stub is proposed here. Efficient coupling has been achieved by means of a single stub microstrip feed between DRA and the feed. The new shape of DRA and a single stub microstrip feed improves the bandwidth significantly as high as 28% from 5 to 6.67 GHz which is quite useful for both WLAN and "C" band applications. The proposed antenna is simple in construction, easy to fabricate, low profile and thickness of CDRA is only 5 mm. A parametric study is performed using Ansoft HFSS simulation software to optimize the antenna performance. The proposed CDRA is fabricated and the characteristics of the antenna are measured.